Surveillance, democracia e direitos humanos: os limites do estado na era do Big Data - Menezes Neto, Elias Jacob de (Universidade do Vale do Rio dos Sinos, 2016)
This thesis stems from the need to properly understand protection of fundamental rights and democracy under the effects of surveillance and global data flows, especially considering that these phenomena are deterritorialized and fluid and, hence, they challenge traditional legal control mechanisms based on the nation-state. For this, it shows how state sovereignty is now affected by the transformations of the nation-state caused by globalization, liquid modernity and the network society. It also explains that surveillance is intrinsic to liquid modernity, which is needed to properly understand the protection of fundamental rights and democracy against global data flows. Thus, it analyses how the word surveillance cannot be directly translated into Portuguese without losing its meaning. In addition, it explains why ideas such as panoptic and Big Brother aren’t enough to understand surveillance in the age of big data. That why it deals with the expansion of surveillance in the twentieth first century and estabilishes how big data and predictive analytics change the meaning of time and space. Based in the war on terror, these techniques try to capture the past and analyse the present in order to predict future events even before they happen. Also, they allow the deterritorialization of nation-state borders, converting them in places to control undesired people flows. For this reason, it shows how the nation-state is weakened on its role of human rights guardian, especially those violated by surveillance, which is why system’s theory and hybrid constitutionalism were considered capable to properly understand human rights violations by information technology transnational organizations. The conclusion points to the idea that human rights cannot be protected against surveillance by traditional legal control mechanisms as they are centered around the idea of the nation-state, which makes it impossible to handle issues that surpass its political system and territorial container, thus requiring private actor to take part in this discussion.
Keywords: Surveillance; Vigilância; Crise do estado; Direitos humanos; Internet; Vigilance; Crisis of the nation-state; Human rights; ACCNPQ::Ciências Sociais Aplicadas::Direito